SPECIFICS OF ORGANIZING SPORTS PROJECTS AT KLITSCHKO FOUNDATION (Physical Culture and Sport: Scientific Perspective, 2025)
Klitschko Foundation is a charitable organization dedicated to youth development through sports, education, and leadership. One of the key areas of the foundation’s work is the organization of sports projects that integrate physical activity, character-building, and leadership skill development. The specificity of Klitschko Foundation's sports projects lies in its comprehensive approach, which goes beyond physical training to include educational components. This article explores the specifics of organizing sports projects at Klitschko Foundation, their impact on Ukrainian youth, and their contribution to civil society development. Klitschko Foundation is one of Ukraine’s leading charitable organizations, implementing educational, sports, and social initiatives. The article analyzes projects such as "Play for Equality", "Success Package", and the "Bloom" educational platform, which focus on promoting physical culture, breaking gender stereotypes in sports, providing psychological support to adolescents, and motivating young people to lead healthy lifestyles. Special attention is given to the social significance of the foundation’s sports programs, their role in shaping active civic engagement among young people, and the overall popularization of sports in Ukraine. The article also examines the impact of the war on children's psychological well-being and the need for charitable initiatives to adapt to modern challenges. The founders, managers, and sponsors of the foundation emphasize their commitment to supporting young people in developing their talents and achieving their dreams. To provide this support, various sports events are organized, a prominent example being the now-regular International Youth Boxing Tournament (Class A), the "Klitschko Tournament", held with the support of the Ministry of Youth and Sports of Ukraine. The authors highlight existing issues the foundation faces, including insufficient transparency in financial reporting and a lack of detailed information on the implementation of certain projects. The article proposes further research directions, including assessing the effectiveness of charitable programs, analyzing youth engagement in sports initiatives, and studying international experiences to scale up the foundation’s activities. This research underscores the vital role of charitable organizations in social development and emphasizes the need to improve operational mechanisms to maximize social impact.
Keywords: target audience; children and youth; online; project activities; sports; success; foundation